Effect of TBM disc-cutter wear on granite rock fragmentation for Kani Sib water-conveyance tunnel project - O'Kelly, Brendan (My University, 2026)
This case-study research article investigates the effects of normal abrasive wear to the disc cutters located in the tunnel-boring machine’s (TBM’s) cutter-head used for excavating through the highly abrasive granite/granodiorite rock mass at the northeast section of the Kani Sib Water-Conveyance Tunnel (KSWCT) project, Iran. The Rock Failure Process Analysis method was employed to investigate the impact of wear (0–20 mm abrasion depth) to single- and double-disc cutters on the rock fragmentation process, integrating Weibull-distributed heterogeneity to the behaviour model. Validated against Brazilian tensile strength test results, the numerical simulations reveal that progressive wear of the cutter blades causes the failure mode for the KSWCT granite rock to transition from efficient brittle fracture (sharp cutters) to energy-intensive ductile-type failure (worn cutters), thereby increasing the peak indentation (cutting) force requirement by 20–40%. Stress distribution analysis demonstrates a sharp concentrated stress profile observed ahead of new disc cutters indenting into intact granite rock, whereas the worn cutters generate diffuse stress fields, delaying rock fragmentation. A 12 mm cutter-wear threshold (beyond which the energy consumption for crack propagation increased by 35%) was identified to mitigate efficiency losses for tunnelling in the KSWCT granite rock, thereby providing a data-driven basis for predictive cutter-disc maintenance in mechanised tunnelling operations.
PUBLISHED
Keywords: Rock failure process; Disc-cutter wear; Rock cutting; Smart & Sustainable Planet; ABRASIVE WEAR; Constitutive modelling in geotechnical engineering; Disc cutter; GEOTECHNICAL ENGINEERING; Geotechnics; Rock Breakdown; Rock Failure Process Analysis; Rock Mechanics; TBM; TUNNELLING; Tunnels; geomechanics; tunnel boring machine; tunneling